Tanggapan Siswa SMP Terhadap Media Pembelajaran IPA Menggunakan Aplikasi Tiktok - Ismi - Mudrikah; Zalfa Az Zahra; Danimaulia Nurraafi Awali; Sukma Ramadhant; Rifani Adelina; Rina Rahayu (Faculty of Teacher Training and Education, Musamus University, 2021)
Online learning is alternative for learning activities during the Covid-19 pandemic by educators. Teachers required to innovate in choosing learning media, so that lessons are not boring and laerning motivation increase. Science learning media must be interesting and easy to understand, so students are accustomed and happy. Tiktok is one of the popular applications that can be used as an interesting and interesting science learning media for students. This research was conducted using qualitative descriptive analysis method. The sample in this study was randomly selected junior high school students totaling 38 childrens. This study aims to determine the response of junior high school students to science learning media using the tiktok application. The results of student responses are : 1) students recognize, use, and assume that the tiktok application has a positive impact, (2) students easily understand tiktok content related to science learning, (3) the majority of teachers have not implemented the tiktok application as a science learning media, and (4) the response of science learning media using the tiktok application received a positive response from junior high school students. The conclusion is tiktok can be used for alternative learning science by teachers because of the positive response from students.